2006
DOI: 10.1111/j.1467-8373.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing the hinterland beyond: Two ideal-type strategies of economic development for small island territories

Abstract: Rarely does one come across critical analysis which looks at islands as the strategic and candid promoters of a role as political and economic usufructuaries over external resources. This paper is premised on the proposition that a small territory is especially obliged to use extraterritorial resources as its hinterland for economic success. Such resources extend over a whole range of goods and services and include access to investment, welfare, security, stable currency, international relations, specialised l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 40 publications
1
59
0
6
Order By: Relevance
“…Num trabalho mais recente (2010), o mesmo autor refere que atualmente existem três perspetivas ao nível da investigação sobre estudos insulares: uma relacionada com a " Nissologia" de McCall (1994, 1996, outra assente na noção de insularidade (Baldacchino, 2004), e, uma terceira, relacionada com o facto de as ilhas se constituírem como laboratórios espaciais.…”
Section: A Importância Científica Das Ilhas: Principais Tendências Aounclassified
See 2 more Smart Citations
“…Num trabalho mais recente (2010), o mesmo autor refere que atualmente existem três perspetivas ao nível da investigação sobre estudos insulares: uma relacionada com a " Nissologia" de McCall (1994, 1996, outra assente na noção de insularidade (Baldacchino, 2004), e, uma terceira, relacionada com o facto de as ilhas se constituírem como laboratórios espaciais.…”
Section: A Importância Científica Das Ilhas: Principais Tendências Aounclassified
“…Numa perspetiva dos estudos insulares que apresenta como referência o conceito de insularidade, Baldacchino (2004) alerta para o perigo tradicional que existe sobre o negativismo associado a esta noção, pois conforme destaca Henriques (2009, p. 13/14) "entre essas "certezas" que costumamos aceitar como categóricas ou definitivas sobre ilhas e a condição insular estão ideias como as de isolamento e solidão, de separação e afastamento, de fechamento e de aprisionamento." Ora, nem sempre este tipo de visão corresponde à realidade, até porque o conceito de insularidade deverá ser considerado com alguma relatividade.…”
Section: A Importância Científica Das Ilhas: Principais Tendências Aounclassified
See 1 more Smart Citation
“…Ironically, it is the cash and value added created in the economically successful 'hot spots' of the world that is often behind the financing needed to purchase, craft and conserve ecological island enclaves. This is another way of tapping 'the hinterland beyond' (Baldacchino 2006b ) . And so, the two sides of the 'eco principle' connect in a rather perverse but symbiotic relationship.…”
Section: Carving Out Islands For Ecological Sustainabilitymentioning
confidence: 99%
“…Since their publication, there has been growing interest in the 'propensity for dependency ' (McElroy & Pearce, 2006) for small insular territories and different studies have indicated that, in the majority of cases, Sub-National Island Jurisdictions (SNIJs) do better than independent islands (Baldacchino & Milne, 2006;Baldacchino, 2006aBaldacchino, , 2006bBertram 1986Bertram , 1993Bertram , 2006Bertram & Watters, 1985;Ogden, 1989;Poirine, 1993Poirine, , 1994Poirine, , 1998Treadgold, 1999;Watters, 1987). As Baldacchino (2006b, p. 862) argues, non-sovereign small isolated islands have developed "creative solutions" to the challenges they face through utilising resources available to them in the 'hinterland' (Baldacchino, 2006a).…”
Section: Introductionmentioning
confidence: 99%